Kewenangan Komite Sekolah Dalam Meningkatkan Mutu Pendidikan Berdasarkan Undang-Undang Sistem Pendidikan Nasional - Ni Kadek Mariani; Erikson Sihotang; Ni Made Rai Sukardi (Institut Nalanda, 2024)
The formation of the School Committee which has been stipulated in the Decree of the Minister of National Education No. 044/U/2002 dated 2 April 2002, is a mandate from Law no. 25 of 2000 concerning the National Development Program (Propenas) for 2000-2004, with the aim that the formation of School Committees can realize school/community-based education management (school/community-based management). The formation of School/Madrasah Committees is stronger from the legal aspect. Community participation through the School Committee has a very strategic position in developing community responsibility for educational progress. An important aspect of community participation through the School Committee is related to building an attitude of awareness of the quality of education in the community and knowing the meaning and importance of the existence of schools for their children. This type of research is Normative and. The aim of this research is to determine the role of school committees in improving the quality of national education services in the education system. Data obtained through several methods, namely to facilitate data analysis, is then interpreted using inductive thinking, namely based on specific knowledge and then a general solution is taken. , so as to produce conclusions that can be accounted for. Based on the results of the analysis of observation data, interviews and documentation obtained, it can be concluded that the role of the School Committee in Improving the Quality of East education can be carried out with the school Committee as an Advisory agency (giving consideration), the school Committee as a Supporting agency (supporting educational service activities, school committee as controlling agency (controlling educational service activities), school committee as mediator (liaison or communication link between the community and the government).